Slovenian Immigrants and the Ethnic Economy in Contemporary Canada - Durnik, Mitja (Two Homelands, 2017)
The Slovenian community in Canada, although a small constitutive element of the current population, has actively contributed to the economic and political development of the second-largest country in the world. Previous studies have only descriptively addressed the role of Slovenian immigrants in the construction of this important economic system. This paper argues that the development within the community has brought about some significant changes in social stratification among its members, specifically with regard to the radical global economic challenges of recent decades. On the other hand, the specific altruistic mission of Slovenian community organisations has remained largely unchanged.